Seashore disturbance and management of the clonal Arctophila fulva : Modelling patch dynamics - Rautiainen, P.; Laine, A.-L.; Aikio, S.; Aspi, J.; Siira, J.; Hyvärinen, M. (2007)
Question: What is the population viability of a critically endangered seashore grass, Arctophila fulva var. pendulina. Location: Liminka Bay, W Finland, 25°21'70 N, 64°51'90 E. Methods: We constructed a matrix population model based on colonization and disappearance events and patch size changes of A. fulva. Patches were divided into hydric and nonhydric zones according to proximity to the seashore and intensity of disturbance. Perturbation analyses were carried out in order to identify transitions critical for population growth. Seed bank and seed germination studies provided background information for the model design. Results: A. fulva patches observed in the more disturbed hydric zone (closest to the sea) increased in number, as did the total number of patches. However, the number of patches in the less disturbed non-hydric zone decreased. Conclusions: Short-term dynamics of the A. fulva population at Liminka Bay seem to be determined by environmental fluctuations, which cause annual variation in transition rates between patch size classes. The long-term dynamics are probably governed by initiation of primary succession by isostatic land uplift. Increased disturbance at the water’s edge may promote persistence of A. fulva through reduced interspecific competition. Our results suggest that shoreline disturbance of the hydric zone is sufficient for maintaining a viable population. Competitive exclusion of A. fulva in the non-hydric zone may be delayed by management practices, such as mowing.